Knowledge and attitudes towards Alzheimer’s disease and related dementias among Nigerian medical and nursing students: a comparative study - Tobi Olajide; Favour Ajao; Inioluwa Joshua; Abigail Oyedokun; Ayosubomi Odubiyi; Oluwadabira Adewara; Feziechi Anele; Ayomide Fatola; Samuel Ayeni; Nneka Amakom; Oluwanifemi Osakuade; Oluwabunmi Adeyeye; et al. (BMC Medical Education)
Abstract Introduction Dementia is a growing public health challenge globally, with low- and middle-income countries, including Nigeria, disproportionately affected. Healthcare professionals play a critical role in dementia care. This study compared the knowledge and attitudes of medical and nursing students at a Nigerian university toward Alzheimer’s Disease and Related Dementias (ADRD). Methods This cross-sectional study was conducted at the College of Medicine University of Ibadan, Nigeria. A total of 143 penultimate and final-year medical and nursing students were selected by stratified random sampling. Data were collected using the Alzheimer’s Disease Knowledge Scale (ADKS) and Dementia Care Attitude Scale (DCAS). Multivariate analysis of variance (MANOVA) was used to compare mean scores between these students. Multivariate regression models were developed to identify factors significantly associated with ADKS and DCAS scores. Statistical significance was determined using a two-tailed p-value of < 0.05. Results The mean age of participants was 22.61 years (SD ± 2.56). Medical students demonstrated significantly higher knowledge scores (19.82, SD ± 3.17) compared to nursing students (17.39, SD ± 2.65; p < 0.001) on a scale of 0 to 30. Attitudes measured using the Dementia Care Attitude Scale (DCAS) showed no significant difference between groups, with medical students scoring slightly higher. Multiple regression analysis identified department as a significant predictor of knowledge (p < 0.001) and attitudes (p = 0.010). Conclusion The study highlights gaps in dementia education among medical and nursing students in Ibadan. Targeted educational interventions, including enhanced curriculum content and experiential learning opportunities, are urgently needed to improve dementia care preparedness in the healthcare workforce.